Development of Arduino-Based Rotating Wheel as a Physics Learning Media of Circular Motion - Putri, Maharani Ayu Nurdiana; Krisnaningsih, Erina; Sya’roni, Imam; Devianti, Wanda (FKIP Universitas Lampung, 2022)
Learning media was used to explain the theory and minimize misconceptions. 50% of physics teachers in East Java have difficulty creating learning media of circular motion. Therefore, researchers created an innovation learning media and analyze the perception of physics teachers to Arduino-based